Kepemimpinan dalam Perspektif Pemikiran Politik Islam - Khoirul Fata, Ahmad (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
The dynamics of the Islamic dynasty take a serious attention of Muslim Thinkers in the past, and they tried to formulate the concept of leadership in accordance with the Islamic idealism. The research looked at how leadership has a great significance for muslims and Islam. According to Islam, the point of urgency lies in realities that leadership is an important factor to achieve the goal of community live. Although the socio-political background of different Muslim Thinkers, this study found the red thread, that in leadership, people realize that the society can exist with values based on Islam. Leadership has a sacred values closely related to how to impose religious values in society and state.